2022
DOI: 10.1111/ejn.15566
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive lipids and their metabolism: New therapeutic opportunities for Parkinson's disease

Abstract: Parkinson's disease (PD) is a neurological disorder characterized by motor dysfunction, which can also be associated with non‐motor symptoms. Its pathogenesis is thought to stem from a loss of dopaminergic neurons in the substantia nigra pars compacta and the formation of Lewy bodies containing aggregated α‐synuclein. Recent works suggested that lipids might play a pivotal role in the pathophysiology of PD. In particular, the so‐called ‘bioactive’ lipids whose changes in the concentration may lead to functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 220 publications
1
6
0
Order By: Relevance
“…6). This agrees with published evidence that lipidomic regulation is supported by evidence for all three classes such as for sphingosine kinase 1 and sphingosine-1-phosphate [47], ceramides and glucosylceramide [48-51], phospholipids [52] and also for lysophosphatidic acids [53][54][55][56]. The isomap projection provided the best basis for a cluster structure that matched the prior class structure, followed by t-SNE, while the other projection methods performed clearly worse (Fig.…”
Section: Metabolomics Data Set For Parkinson Diseasesupporting
confidence: 90%
“…6). This agrees with published evidence that lipidomic regulation is supported by evidence for all three classes such as for sphingosine kinase 1 and sphingosine-1-phosphate [47], ceramides and glucosylceramide [48-51], phospholipids [52] and also for lysophosphatidic acids [53][54][55][56]. The isomap projection provided the best basis for a cluster structure that matched the prior class structure, followed by t-SNE, while the other projection methods performed clearly worse (Fig.…”
Section: Metabolomics Data Set For Parkinson Diseasesupporting
confidence: 90%
“…It has been shown that in a specific brain region of patients affected by severe PD, there was a significant increase in the expression of enzymes involved in Cer synthesis [ 93 ]. Moreover, Cer levels have been associated not only with the pathogenesis of PD but they have also been correlated with cognitive function [ 94 ].…”
Section: Ceramide and Sphingosine-1-phosphate In Neurodegenerative Di...mentioning
confidence: 99%
“…On these bases, the inhibition of Cer signaling could be an important target for new therapies for PD. It has been shown that, in an in vitro PD model, SphKs and S1P lyase gene expression was significantly altered and that the cytosolic SphK1 and nuclear SphK2 activities were significantly reduced [ 94 , 96 , 97 , 98 ]. Several papers have shown that FTY720 prevented the loss of DA neurons in 6-hydroxydopamine-, rotenone- and acute 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD cellular and animal models [ 99 , 100 , 101 , 102 ].…”
Section: Ceramide and Sphingosine-1-phosphate In Neurodegenerative Di...mentioning
confidence: 99%
See 2 more Smart Citations